The gods of Mars [compact disc, unabridged] - Burroughs, Edgar Rice, 1875-1950 (Burroughs, Edgar Rice, 1875-1950. John Carter of Mars., 2009)
After ten long years, John Carter is finally transported back from Earth to Mars where he hasn't seen his wife Dejah Thoris or their child. Unfortunately, John materializes in the Valley Dor, the Barsoomian heaven which no one is ever allowed to escape.